Cultivation-dependent plasticity of melanoma phenotype - Kodet, Ondřej; Dvořánková, Barbora; Krejčí, Eliška; Szabo, Pavol; Dvořák, Petr; Štork, Jiří; Krajsová, Ivana; Dundr, Pavel; Smetana, Karel; Lacina, Lukáš (Tumour biology, 2013)
Malignant melanoma is a highly aggressive tumor with increasing incidence and high mortality. The importance of immunohistochemistry in diagnosis of the primary tumor and in early identification of metastases in lymphatic nodes is enormous; however melanoma phenotype is frequently variable and thus several markers must be employed simultaneously. The purposes of this study are to describe changes of phenotype of malignant melanoma in vitro and in vivo and to investigate whether changes of environmental factors mimicking natural conditions affect the phenotype of melanoma cells and can revert the typical in vitro loss of diagnostic markers. The influence of microenvironment was studied by means of immunocytochemistry on co-cultures of melanoma cells with melanoma-associated fibroblast and/or in conditioned media. The markers typical for melanoma (HMB45, Melan-A, Tyrosinase) were lost in malignant cells isolated from malignant effusion; however, tumor metastases shared identical phenotype with primary tumor (all markers positive). The melanoma cell lines also exerted reduced phenotype in vitro. The only constantly present diagnostic marker observed in our experiment was S100 protein and, in lesser extent, also Nestin. The phenotype loss was reverted under the influence of melanoma-associated fibroblast and/or both types of conditioned media. Loss of some markers of melanoma cell phenotype is not only of diagnostic significance, but it can presumably also contribute to biological behavior of melanoma. The presented study shows how the conditions of cultivation of melanoma cells can influence their phenotype. This observation can have some impact on considerations about the role of microenvironment in tumor biology.
Keywords: melanomový antigen gp100; gp100 Melanoma Antigen; MART-1 antigen; nádory kůže; Humans; Skin Neoplasms; Tumor Cells, Cultured; kokultivační techniky; melanom; Biomarkers, Tumor; Melanoma-Specific Antigens; Models, Biological; imunofenotypizace; Nestin; lidé; tyrosinasa; Cells, Cultured; Immunohistochemistry; imunohistochemie; nádorové buňky kultivované; nádorové biomarkery; Coculture Techniques; MART-1 Antigen; Immunophenotyping; S100 Proteins; Melanoma; kultivované buňky; nestin; biologické modely; Tumor Microenvironment; nádorové buněčné linie; nádorové mikroprostředí; fibroblasty; melanomové antigeny; buněčné kultury; Cell Culture Techniques; Cell Line, Tumor; Monophenol Monooxygenase; Culture Media, Conditioned; kultivační média speciální; Fibroblasts; proteiny S100